Dental health in ancient Egypt - Judith Miller (Journal of Biological Research, 2021)
The Ancient Egyptians suffered from devastating dental disease through the millennia and this may have caused premature mortality. The changes in types of dental disease were influenced by the transformation of life from hunter-gatherers to settled agriculturists and the introduction of new crops. The supply of crops was also affected by periods of famine caused by flooding or drought. Over 500 skulls from different geographical regions and time periods were examined for this study and examples of caries, premature loss of teeth and abscesses will be shown. Age at death has been calculated from the dentition. Although there were seven individuals with the title of “dentist”, their role is uncertain and an apparent lack of effective treatment has been observed despite dental prescriptions in the medical papyri.